Entre vivre et survivre, la rencontre d’Hiroshima mon amour - Cavallo, Valérie (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
Written by Marguerite Duras and directed by Alain Resnais, the movie Hiroshimamon amour is set in the immediate post-war period, precisely in the Japanese citydestroyed by the first nuclear bombardment while life is trying to begin again. Consideringthe immense wounds inflicted on the anonymous people of all nations duringthe Second World War, the scenario proposes to oppose this unprecedented catastrophewith a romantic encounter in which the authors attempt to identify the irreducibility ofaffects and feelings as a condition for renewing the living of a fractured humanity that ismore sensitive than ever.